Antarctic killer whales make rapid, round-trip movements to subtropical waters: evidence for physiological maintenance migrations? - Durban, J. W. (The Royal Society, 2012)
Killer whales (Orcinus orca) are important predators in high latitudes, where their ecological impact is mediated through their movements. We used satellite telemetry to provide the first evidence of migration for killer whales, characterized by fast (more than 12 km h(−1), 6.5 knots) and direct movements away from Antarctic waters by six of 12 type B killer whales tagged when foraging near the Antarctic Peninsula, including all tags transmitting for more than three weeks. Tags on five of these whales revealed consistent movements to subtropical waters (30–37° S) off Uruguay and Brazil, in surface water temperatures ranging from −1.9°C to 24.2°C; one 109 day track documented a non-stop round trip of almost 9400 km (5075 nmi) in just 42 days. Although whales travelled slower in the warmest waters, there was no obvious interruption in swim speed or direction to indicate calving or prolonged feeding. Furthermore, these movements were aseasonal, initiating over 80 days between February and April; one whale returned to within 40 km of the tagging site at the onset of the austral winter in June. We suggest that these movements may represent periodic maintenance migrations, with warmer waters allowing skin regeneration without the high cost of heat loss: a physiological constraint that may also affect other whales.